Anorectal dysfunction after laparoscopic low anterior rectal resection for rectal cancer with and without radiotherapy (manometry study). Issue 4 (1st November 2017) - Ihnát, Peter; Slívová, Ivana; Tulinsky, Lubomir; Ihnát Rudinská, Lucia; Máca, Jan; Penka, Igor
Abstract : Background and Objectives: The aim was to evaluate the impact of radiotherapy (RT) on anorectal function of patients with low rectal cancer undergoing low anterior resection (LAR). Methods: Prospective clinical cohort study conducted to assess the functional outcome by means of high‐resolution anorectal manometry and LARS score. Results: In total, 65 patients were enrolled in the study (27 patients underwent LAR without RT, 38 patients underwent RT and LAR). There were no statistically significant differences between study subgroups regarding demographic and clinical data; postoperative morbidity was significantly higher in irradiated patients. One year after the surgery, mean LARS score was significantly higher in patients who underwent RT and surgery. Major LARS was detected in 37.0% of irradiated patients and in 14.8% of patients after surgery alone. Anorectal manometry revealed significantly lower resting pressures in patients after RT and LAR; the squeeze pressures were similar. Rectal compliance and all volumes describing rectal sensitivity (first sensation, urge to defecate, and discomfort volume) were significantly lower in irradiated patients. Conclusions: RT significantly deteriorates the functional outcome of patients after LAR. Manometry revealed internal sphincter dysfunction, reduced capacity, and compliance of neorectum, which seem to have a significant correlation with LARS presence/seriousness.